USE OF STERILE WATER FOR INJECTION IN THE MANAGEMENT OF LABOR PAIN: A RANDOMIZED CONTROLLED TRIAL - MAZUMDER, PALASH; PANDEY, SWADHA; MANDI, DEBJIT; DUTTA, SHYAMALI (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: The objectives of the study are to assess the efficacy of sterile water for injection (SWI) in reducing labor pain, compare it with a saline procedure, and see which one is superior. Parameters assessed were pain relief based on the numeric pain rating scale (NPRS) and duration of labor from intervention to delivery associated with administration of subcutaneous SWI versus normal saline injection (NSI). Methods: This is a prospective randomized interventional hospital-based comparative study of mothers who were in active labor with back pain and undergoing treatment in the labor room of Eden Hospital, Medical College and Hospital, Kolkata. The study was conducted on 66 willing pregnant mothers, divided into two groups of 33 each with one injected with normal saline and the other with sterile water. Results: The NPRS score was almost equal in 2 groups at 15 min, but with an increase in duration, it was seen that the score was low in the sterile water group compared to the normal saline group. The association was statistically significant (p<0.05). Conclusion: This study hypothesized that subcutaneous SWI for relieving labor pain is better than subcutaneous NSI. Based on this study, it is concluded that both the SWI and NSI reduce labor pain, but the SWI produced a significantly greater reduction of pain as measured by the numeric pain rating score and also better satisfaction. Therefore, SWI is a safe, simple, and cost-effective method and can be used as a pain-relieving method, especially in the absence of other pain-relieving options.